2020
DOI: 10.1039/c9gc03545a
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving used rubber tires

Abstract: Reductive silylation cleaves S–S crosslinks in used automotive rubbers, allowing recovery of polymeric oils in up to 93% yield. The oils can undergo oxidative crosslinking to give new elastomers, closing the loop for sulfur-cured rubbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…[ 6 ] We recently demonstrated that the automobile rubber—crosslinked by oligosulfides—could be converted to polymeric oils by reduction of the S–S bonds. [ 7 ] Could such a redox process be the basis of reusable thermoset silicone elastomers?…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] We recently demonstrated that the automobile rubber—crosslinked by oligosulfides—could be converted to polymeric oils by reduction of the S–S bonds. [ 7 ] Could such a redox process be the basis of reusable thermoset silicone elastomers?…”
Section: Figurementioning
confidence: 99%
“…In previous work, we reported a versatile, inexpensive method to reduce organic disulfide bonds with hydrosilanes. [ 13 ] We were interested to apply this method reversibly in redox sensitive silicone polymer networks.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…16 Cyclic tri-and tetrasulfanes are also known to be available using methodology A, and have been fully reviewed, 1 but once again, mixtures of polysulfanes are invariably produced as with the acyclic variants (Scheme 1, entries 4 and 5). 17,18 Scheme 1 illustrates entries 1-5 based on examples from the last twenty years or so.…”
Section: Review Synopenmentioning
confidence: 99%
“…In his extensive and elegant studies of reduction of carbonyl groups, Piers showed that it was also a potent catalyst for hydrosilane reductions [ 17 ]. We used M H M H in the presence of BCF to reduce the sulfur crosslinks in automobile rubber tires, permitting reuse of the organic constituents [ 19 ]. When using HSiEt 3 in the presence of BCF, Piers et al originally reported that over-reduction of carbonyl groups led first to silyl ethers and then to alkanes plus disiloxanes.…”
Section: Introductionmentioning
confidence: 99%